The role of training human resources in the elements of administrative innovation - كاظم, عمار جبار (Journal of Economics and Administrative Sciences, 2019)
The current research aims to identify the nature of the relationship between training human resources in administrative innovation elements In the General Directorate for the education of the third Rusafa one of the formations of the Iraqi Ministry of Education in Baghdad, In order to achieve the objectives of the research, the researcher provided a comprehensive theoretical framework and the preparation and development of a questionnaire as a tool for collecting data based on the prepared measurements and benefit from previous studies, which contains (28) For the purpose of obtaining realistic results for the variables of the research, the researcher used the random sample in the selection of the research sample A total of (63) questionnaires were distributed in the researched Directorate, and (58) Using a set of scientific statistical methods (SPSS: V-24) and Excel (V-2013) in order to analyze the data obtained through the questionnaire and some personal interviews in statistical methods, After completing the process of statistical data analysis and test hypothesis research, The results of the study showed the existence of a significant correlation between the training of human resources and the elements of administrative creativity in the Directorate of the research The researcher recommended the need to adopt the results and recommendations of the research by the Directorate of research and directorates and other similar companies in order to enhance administrative creativity in the personnel working in the organization through the training function one of the most important functions of human resources management.